Hybrid Technique Based Blind Digital Image Watermarking (International Journal of Engineering and Computer Science, 2017)
Nowadays Internet is an excellent priority base source for everyone for sales and distribution and everything for digital assets, but because of this world wide sharing of digital information now there is an issue of copyright compliance and content management can be a challenge for us. Now a digital information can be used everywhere very easy way with or without using consent. Digital image Watermarking is an ultimate solutions that can add an extra security layer of protection for a digital images. In a digital image watermarking technique an image or an object embedded with some information carrying watermark, this object may be audio or video. These watermarking embedded techniques based on DWT –Twin Encoding technique drive the benefits from random sequence generated by Arnold and Chaos transformations. The proposed system before sending the multimedia data it apply the composite partition algorithm, watermark optimization techniques and the resulting file is Encrypted using RSA algorithm with public key and send it to the client side. Simulation result shows the performance of watermarking of image against different attacks. In the end, the performance of the proposed technique will be measured on the basis of PSNR, and NCC